A tale of two lakes: a multi‐proxy comparison of Lateglacial and Holocene environmental change in Cappadocia, Turkey. (17th June 2016) - Roberts, Neil; Allcock, Samantha L.; Arnaud, Fabien; Dean, Jonathan R.; Eastwood, Warren J.; Jones, Matthew D.; Leng, Melanie J.; Metcalfe, Sarah E.; Malet, Emmanuel; Woodbridge, Jessie; Yiğitbaşıoğlu, Hakan
ABSTRACT: Individual palaeoenvironmental records represent a combination of regional‐scale (e.g. climatic) and site‐specific local factors. Here we compare multiple climate proxies from two nearby maar lake records, assuming that common signals are due to regional‐scale forcing. A new core sequence from Nar Lake in Turkey is dated by varves and U–Th to the last 13.8 ka. Markedly dry periods during the Lateglacial stadial, at 4.3–3.7 and at 3.2–2.6 ka BP, are associated with peaks in Mg/dolomite, positive δ 18 O, elevated diatom‐inferred electrical conductivity, an absence of laminated sediments and low Quercus /chenopod ratios. Wet phases occurred during the early–mid Holocene and 1.5–0.6 ka BP, characterized by negative δ 18 O, calcite precipitation, high Ca/Sr ratios, a high percentage of planktonic diatoms, laminated sediments and high Quercus /chenopod ratios. Comparison with the record from nearby Eski Acıgöl shows good overall correspondence for many proxies, especially for δ 18 O. Differences are related to basin infilling and lake ontogeny at Eski Acıgöl, which consequently fails to register climatic changes during the last 2 ka, and to increased flux of lithogenic elements into Nar Lake during the last 2.6 ka, not primarily climatic in origin. In attempting to separate a regional signal from site‐specific 'noise', two lakes may therefore be better than one.